La televisión en el aprendizaje de los niños y niñas del quinto, sexto y séptimo año de educación básica de la "Unidad Educativa de Guapara" del recinto Guapara parroquia Moraspungo cantón Pangua provincia de Cotopaxi en el período lectivo 2010 - 2011 - Gaibor Mora, Miguel Angel (2011)
It doesn't fit doubt that today in day the television has become partly substantial of our lives, so much of adults as of children and girls, and that every time it influences with more force in the behavior and attitude of the same ones, but mainly in these last ones, because in many homes they are allowed to see television excessively, since there are many unworried and comfortable parents that when not assuming its list fully, they induce the children at long hours to pass in front of the television, the same one that completes nanny's paper in many cases. Today more than ever becomes remarkable the influence of television in the children and girls, since this he/she has gone winning him spaces to other such activities of distraction as games outdoors, practical sport, reading, to listen histories and stories next to the parents, etc. the same ones that helped them in their intellectual, psychic and physical development, because these interactuaban with their parents and with the other children and girls of their age. This problem affects the academic yield and the behavior of the children and girls seriously, for that reason we decide to carry out our investigation basing us on this topic and the place that we chose it was the “EDUCATIONAL UNIT DE GUAPARA” and with the group that we decide to work they were the students of fifth, sixth and seventh years of Basic Education, because many of them present problems in its studies and behavior, caused primarily by the excess of time dedicated to do television with programs of terrible content as the Power Rangers or Dragón Ball Z, action movies, novels, programs for adults, loaded with violent acts as murders, wars, blows, destruction, sex scenes, among other, those that damage its mentality, since the children and girls imitate what come in television, ignoring the difference between the real thing and the fantasy, among the possible and impossible they spread since to be identified with the values that the characters of television reflect, for example of the violent heroes they adopt norms that are imposed by the force and antisocial relationships in front of their fellow men, we can also mention to the terror programs, since these contents cause in them, nightmares and fears, those that affect its concentration and for ende its yield in the studies. All the previously this one, allows clearly to see the great problem that is causing the children and girls to see television excessively and mainly programs that propitiate the violence and that they have first floor moral, ethical content and of values, but we should also take into account that the television is a real fact and that it is very bound to us and that not all that projects is bad, and that to prohibit it would be a too definitive measure that would propitiate another type of inconveniences to the long one. It is for that reason that we as professional futures of the education, want to be you participate of the positive changes of our society, it is for that reason that our projects are not guided alone to detect the causal of the problem, but also to look for the most appropriate solutions that allow to remedy or to alleviate in something this situation, for what we consider opportune to work jointly between teachers and family parents, and together with a professional in psychology, to plan chats and conferences stops then to socialize them with the children and the recruit's girls, sixth and seventh Year of Basic Education of the “EDUCATIONAL UNIT DE GUAPARA, to make them know, to learn and to understand on the negative effects that the television excess can generate in its psychological, affective and educational formation.